A comparison of the risk of postoperative recurrence between African‐American and Caucasian patients with Crohn's disease. Issue 9 (20th August 2018) - Anyane‐Yeboa, Adjoa; Yamada, Akihiro; Haider, Haider; Wang, Yunwei; Komaki, Yuga; Komaki, Fukiko; Pekow, Joel; Dalal, Sushila; Cohen, Russell D.; Cannon, Lisa; Umanskiy, Konstantin; Smith, Radhika; et al.
Summary: Background: Many patients with Crohn's disease will develop complications that require surgery. Recurrence after surgery is common. Aim: To assess racial differences in postoperative recurrence between African‐Americans and Caucasians. Methods: Medical records of Crohn's disease patients who underwent surgery (ileal, colonic, or ileocolonic resection) between June 2014 and June 2016 were reviewed. The primary endpoints were clinical and endoscopic remission at 6‐12 months after a Crohn's disease surgery. Secondary outcomes included biological and histologic remission. Risks of recurrence were assessed by univariate, multivariate, and propensity score‐matched analysis. Results: Thirty‐six African‐American and 167 Caucasian patients with Crohn's disease were included for analysis. There was no difference in disease location, disease behaviour, type of surgery performed, and pre‐ or postoperative medication use between the two groups. The rate of endoscopic remission did not differ between African‐American and Caucasian patients (50% vs 42%, P = 0.76), and race did not influence the risk of endoscopic recurrence on univariate, multivariate, or propensity score‐matched analysis. The rate of clinical remission was significantly lower in African‐American patients compared to Caucasian patients (36% vs. 63%, P = 0.008). African‐American race was significantly associated with clinical recurrence on univariate (odds ratio (OR) 6.76, 95% CI 1.50‐30.40; P = 0.01), multivariate (OR 5.02, 95% CI 1.60‐15.80; P = 0.006), and propensity‐matched analysis (68% vs. 32% in Caucasians, P = 0.005). Rates of biologic and histologic remission were similar between the two groups on all analyses. Conclusions: We found that African‐American patients with Crohn's disease have a similar degree of objective measures of mucosal inflammation after surgery including endoscopic recurrence as compared to Caucasian patients. However, African‐American race was significantly associated with clinical recurrence, suggesting the presence of ethnic variation in postoperative presentation in Crohn's disease.